Angular‐Multiplexing Metasurface: Building Up Independent‐Encoded Amplitude/Phase Dictionary for Angular Illumination. Issue 22 (2nd September 2021) - Wan, Shuai; Wan, Chengwei; Dai, Chenjie; Li, Zhe; Tang, Jiao; Zheng, Guoxing; Li, Zhongyang
Abstract: As metasurfaces have shown great potential for light manipulation, the majority of optical source parameters have been extensively explored and progressively realized for new degrees of freedom in optical control and multiplexing, including wavelength, polarization, and forward/backward illumination, etc. However, the incident wave vector ( k ) direction, namely the illumination angle, as one of the critical parameters, has not been fully explored for optical multiplexing due to the lack of angular‐encoding freedom. Here, a general strategy is proposed to realize angular‐multiplexing metasurface based on building up an independent‐encoded amplitude/phase dictionary, in which one can retrieve any arbitrary combination of optical response with different angular illuminations. A series of angular‐multiplexing designs are theoretically and experimentally demonstrated, including angular‐multiplexed meta‐holographs, nanoprintings as well as a hybridized nanoprinting with holography. These studies' numerical calculations and experiments confirm the new degree of freedom for arbitrary encoded amplitude and phase at different illumination angles. The findings establish a new platform for achieving a complexity of functions for angular resolved illumination, and expanding the manipulative capabilities for optical multiplexing. Abstract : A general strategy for designing angular‐multiplexing metasurface is proposed, and the essential mechanism is building up independent‐encoded amplitude/phase dictionary. A series of the independent angular‐multiplexing designs are theoretically and experimentally demonstrated including angular‐multiplexed holographs, nanoprinting as well as hybridized nanoprinting with metaholography. These studies establish a new platform for expanding the manipulative capabilities for angular multiplexing.